From tissue-specific to tissue-agnostic: HER2 overexpression and the rise of antibody-drug conjugates - Ko, Heidi C.; Strickland, Kyle C.; Jaggessarsingh, Dana; Dillard, Alicia; Green, Michelle; Newburn, Erin; Sellaro, Tiffany; Klein, Jonathan L.; Caveney, Brian; Eisenberg, Marcia; Severson, Eric A.; Ramkissoon, Shakti; et al. (Frontiers in Oncology, 2025)
The growing importance of HER2 expression as a biomarker across multiple cancers is largely driven by advances in HER2-directed antibody-drug conjugates. The recent approval of trastuzumab deruxtecan (T-DXd) as a tumor-agnostic therapy has revolutionized treatment strategies for HER2-overexpressed tumors beyond breast, gastric, and colorectal cancers (CRC). This mini-review explores the evolving role of assessing HER2 overexpression in pan-solid tumors, following the recent approval of T-DXd as a tumor-agnostic therapy. It examines how HER2 scoring criteria for pan-tumor indications rely on immunohistochemistry (IHC) assessment, which may be prone to subjective interpretation and interobserver variability, and how these criteria differ from those used in breast, gastric, and CRC tumors. We also address the potential for NGS approaches to identify ERBB2 copy number gain (CNG) and the utility of artificial intelligence (AI) algorithms to enhance the consistency and accuracy of HER2 score interpretation for T-DXd treatment eligibility in solid tumors.